Secular-Islamist cleavage, values, and support for democracy and shari’a in the Arab world - Ciftci, Sabri (My University, 2014)
Public opinion polls demonstrate that Arab citizens support both democracy and shari’a. I argue that individual values related to the secular-Islamist cleavage are instrumental in explaining this joint support. The analysis of the Arab Barometer survey shows that individuals holding Islamic values are more favorable of shari'a whereas those with secularist values tend to support democracy. However, the bivariate probit estimations also confirm that Arab opinion about these governing principles is more complementary and less divergent. The results imply that constitutional models combining Islam and democracy, rather than strictly secular institutions, may be more acceptable to Arab citizens.
Keywords: Shari’a; Democracy; Islam; Secular; Arab attitudes; Bivariate probit; Values